Global methylation in ‘Valencia’ orange seedlings associated with rootstocks and Huanglongbing - Rodrigues, M. G.F. [UNESP]; Nakanishi, E. S. [UNESP]; Soutello, R. V.G. [UNESP]; Diniz, F. O.N.H. [UNESP] (FapUNIFESP (SciELO), 2023)
Citrus farming is one of the main activities that contributed to the Brazilian trade balance, with citrus seedling being the most important input in the formation of orchards to guarantee high productivity and fruit quality, which fundamentally depends on the chosen genetics. The present study aimed to analyze the existence of epigenetic variability in ‘Valencia’ orange plants on rootstocks, associated or not with HLB, through the quantification of the global methylation of its genome, in order to support works on genetic improvement and crop production. For this purpose, this work was carried out in greenhouse in a completely randomized experimental design, with 5 treatments and 6 replicates per treatment, each seedling being considered a replicate, namely: T1 = “Valencia” orange grafted onto “Rangpur” lemon, inoculated with HLB; T2 = “Valencia” orange grafted onto “Swingle” citrumelo, inoculated with HLB; T3 = “Valencia” orange grafted onto “Rangpur” lemon, without HLB inoculation; T4 = “Valencia” orange grafted onto “Swingle” citrumelo, without HLB inoculation; T5 = “Valencia” orange in free standing. The DNA was extracted from leaves and the ELISA test (Enzyme-Linked Immunosorbent Assay) was carried out, based on the use of receptors sensitive to 5-mC., to measure the relative quantification of global methylation between genomic orange DNAs. Since the control treatment (T5) consists of “Valencia” orange in free standing, it could be inferred that both the normal grafting technique in the seedling formation process and the inoculation of buds infected with HLB are external factors capable of changing the methylation pattern in the evaluated plants, including the DNA demethylation process, causing an adaptive response in association with the expression of genes previously silenced by genome methylation.
Metilação global em mudas de laranja valência associadas a porta-enxertos e ao Huanglongbing
Keywords: citrus culture; epigenetics; phenotypic plasticity